2020
DOI: 10.1101/2020.07.11.197798
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasticity in prefrontal cortex induced by coordinated nucleus reuniens and hippocampal synaptic transmission

Abstract: The nucleus reuniens of the thalamus (NRe) is reciprocally connected to a range of higher order cortices including hippocampus (HPC) and medial prefrontal cortex (mPFC). The physiological function of NRe is well predicted by requirement for interactions between mPFC and HPC, including associative recognition memory, spatial navigation and working memory. Although anatomical and electrophysiological evidence suggests NRe makes excitatory synapses in mPFC there is little data on the physiological properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 87 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…Changes in timing between mono- (Re→mPFC) and disynaptic (Re→vCA1→mPFC) inputs to mPFC could result in impairments in input timing-dependent plasticity (ITDP) (e.g., [ 70 , 71 ]) and ultimately learning. In a recent first investigation of this phenomenon, Banks, Warburton [ 19 ] demonstrated that the majority of layer 5 pyramidal neurons in the prelimbic subregion of mPFC receive input from both Re and vCA1. The same study further demonstrated (in ex vivo brain slices) that precise temporal coordination of vCA1→mPFC and Re→mPFC inputs resulted in NMDA-mediated ITDP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Changes in timing between mono- (Re→mPFC) and disynaptic (Re→vCA1→mPFC) inputs to mPFC could result in impairments in input timing-dependent plasticity (ITDP) (e.g., [ 70 , 71 ]) and ultimately learning. In a recent first investigation of this phenomenon, Banks, Warburton [ 19 ] demonstrated that the majority of layer 5 pyramidal neurons in the prelimbic subregion of mPFC receive input from both Re and vCA1. The same study further demonstrated (in ex vivo brain slices) that precise temporal coordination of vCA1→mPFC and Re→mPFC inputs resulted in NMDA-mediated ITDP.…”
Section: Discussionmentioning
confidence: 99%
“…Given this precise regulation of differential timing between HPC and Re inputs to mPFC necessary for ITDP (approximately 10ms according to Banks, Warburton [ 19 ]), it follows that damaging Re and altering the proportion of projection neurons in Re that collaterally innervate vCA1 and mPFC would be likely to influence EF through impaired mPFC function (e.g., [ 13 , 20 ]). This would also account for sparing of orbitofrontal function of any behaviorally-relevant wave of secondary damage from developmental AE (i.e., lack of reversal learning deficit in [ 13 ]), as there have been no observations of Re neurons collaterally projecting to both vHPC and orbitofrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ReRh are involved in associative recognition memory and working memory and have strong reciprocal connections with both HPC and mPFC (Barker & Warburton 2018, Cassel et al 2013, Dolleman-van der Weel et al 2019, Hallock et al 2016 but little is known of how HPC and ReRh inputs converge onto cells in mPFC and how this regulates synaptic plasticity within mPFC (Viana Di Prisco & Vertes 2006). By using a combination of optogenetic stimulation of ReRh inputs and electrical stimulation of HPC inputs (Fig 3A ) we were able to investigate in slices of mPFC whether HPC and NRe inputs converge at the single cell level, characterise receptor physiology at these synapses and determine whether interaction of these inputs results in synaptic plasticity which may allow encoding of information in mPFC (Banks et al 2020).…”
Section: Hippocampal To Prefrontal Cortex Communicationmentioning
confidence: 99%